(untitled) (Biodiversitas Journal of Biological Diversity, 2021)
Abstract. Heriza S, Buchori D, Harahap IS, Maryana N. 2021. Response of termite communities to natural forest conversion. Biodiversitas 22: 5092-5096. Natural forest conversion can affect termite communities resulting from the various types of land use conversion. This study aims to examine the impacts of natural forest conversion on termite communities based on species richness, feeding groups, and termite species composition. Four land use types were evaluated on a gradient from the least to the most disturbing: natural forest, plantation forest, oil palm plantations and settlements. The method used to observe termites in this study is a plot measured 50 m x 10 m and was divided into sub-plots of 5 m x 5 m. The termites were collected from leaf litter and soil, dead wood, trunks, and nests. The response of the termite community to the conversion of natural forest functions into other forms of land use types, where for termite species richness, there was no significant differences between land uses, but for abundance and based on feeding groups there were difference between them.